Pelatihan Media Pembelajaran Berbasis Artificial Intelligence Sebagai Media Penunjang Pembelajaran Madrasah Aliyah Nurul Islam Mandastana - Karyadiputra, Erfan; Setiawan, Agus (CV. Akira Java Bulu, 2025)
The transformation of learning systems due to the Coronavirus Disease 2019 (Covid-19) pandemic has pushed educational institutions to adopt digital technologies, including Artificial Intelligence (AI). However, not all educators particularly in madrasahs have the necessary understanding and skills to utilize AI as a learning medium. This community service program aimed to enhance the competencies of teachers at Madrasah Aliyah Nurul Islam Mandastana in understanding and implementing AI-based learning tools. The method used was Participatory Action Research (PAR), consisting of three main stages: socialization, training and mentoring, and independent practice. Evaluation was carried out using pre-tests and post-tests, as well as direct observation. The results indicated a significant improvement in participants’ competencies, with an average increase of 55,10%. Additionally, the program led to positive changes in teaching approaches, improved student motivation, and enhanced accessibility to learning materials. In conclusion, the AI-based training successfully addressed the technological competency gap among teachers and contributed positively to the madrasah’s teaching and learning practices.